Bioactive secondary metabolites from a soybean-derived fungus Aspergillus versicolor IMBC-NMTP02. (October 2021) - Quang, Tran Hong; Phong, Nguyen Viet; Anh, Dang Viet; Hanh, Tran Thi Hong; Cuong, Nguyen Xuan; Ngan, Nguyen Thi Thanh; Trung, Nguyen Quang; Oh, Hyuncheol; Nam, Nguyen Hoai; Minh, Chau Van
Graphical abstract: Highlights: Isolation of 10 compounds from Aspergillus versicolor IMBC-NMTP02. Structural identification of 3 new, 2 new natural, and 5 known compounds. Cytotoxicity toward HepG2, KB, HL-60, MCF-7, SK-Mel-2, and LNCaP cancer cells. Nitric oxide inhibitory effects of the isolated compounds. Antimicrobial effects of the isolated compounds. Abstract: In the present study, 10 secondary metabolites, including three new asperversilactones A–C (2, 4, and 5 ) and two new natural metabolites (4 Z, 6 S, 7 R )-6, 7-dihydroxyocta-2, 4-dien-4-lactone (1 ) and (4 E, 6 S, 7 R )-6, 7-dihydroxyocta-2, 4-dien-4-lactone (3 ) were isolated from a culture fermentation of the soybean-derived fungus Aspergillus versicolor IMBC-NMTP02. Their structures were elucidated by comprehensive analyses of spectroscopic methods, including NMR, mass, and ECD spectra. Compounds 5, 6, and 9 were shown to have cytotoxic effects toward the HepG2, KB, HL-60, MCF-7, SK-Mel-2, and LNCaP human cancer cell lines (IC50 = 31.7–81.5 μM), whereas all of the compounds inhibited NO overproduction in LPS-stimulated BV2 cells (IC50 = 19.0–41.9 μM). Furthermore, all of the compounds showed antimicrobial effects against Enterococcus faecalis and Candida albican s, with MIC values in the range of 32–256 μM. Our investigation contributes to clarification of the chemical constituents of the soybean-derived A. versicolor and warrants further studies of some bioactive metabolites for therapeutic uses.